Team Mental Models, Team Goal Orientations, and Information Elaboration, Predicting Team Creative Performance. Issue 4 (2nd October 2018) - Toader, Andra F.; Kessler, Thomas
Abstract : This study aimed to enhance understanding of team creativity by investigating the type of team mental models that team members develop during their work on a creative problem solving task. We hypothesized that teams that develop dissimilar team mental models, compared to similar and complementary team mental models, will achieve a higher information elaboration. This effect will be moderated by the development of a high learning-performance team goal orientation. Information elaboration in turn was hypothesized to predict team creative performance. In a 3 (similar/dissimilar/complementary team mental models) × 3 (learning/performance/learning-performance goal orientation) experimental study on a sample of 33 teams ( N  = 98) we found that teams that developed more dissimilar team mental models and experienced a learning-performance goal orientation intervention engaged in more information elaboration. Information elaboration, in turn, mediated the relationship between the interaction between team mental models and team goal orientations and team creative performance. Implications for research on team mental models and team creativity are discussed.